Real-time visualisation and optimisation of acoustic waves carrying orbital angular momentum. (1st July 2022) - Lin, Po-Cheng; Gibson, Graham M; Padgett, Miles J
Abstract: Travelling waves, such as light and sound, can carry angular momentum. Orbital angular momentum (OAM) is one of the components which is determined by the helicity of the phase fronts. The helical waveform is characterised in terms of an integer l and an azimuthal phase term of exp(−i lθ ), but for | l | > 1 the resulting high-order beam structure is unstable to perturbation. In this work, using Fourier transform profilometry and stroboscopic imaging techniques, we demonstrate the real-time visualisation of the OAM-carrying acoustic waveform by imaging the pressure imprint of the acoustic wave on a thin rubber sheet. Furthermore, based on the visualised waveform, we are able to optimise high-order (| l | > 1) OAM states by controlling the individual elements of the acoustic source. Beyond the study of acoustic OAM, the real-time monitoring and optimising methods could be a benefit to other applications requiring acoustic waveform shaping, such as acoustic communications, acoustic holograms, etc.